Economics of a Nordic paper mill–case study. - Esa Hämäläinen; Ulla Tapaninen (Emerald Group Publishing Limited, 2022)
Purpose – The aim of this case study is to reveal the development of prices, costs and logistics in the case mill and how do these variables correlate with profits and finally to give suggestions for improvements.
Design/methodology/approach – We selected a typical Finnish paper mill as the basis for the case study. The mill data contains complete years from 2001 to 2007 on a monthly level. The data was obtained from the mill’s economic system and transferred to Excel. Statistica 4.1 was used to run the statistical correlation analyses. The results can be generalized with certain limitations to paper manufacturing located far from its customers.
Findings – This paper reveals an important insight on the economics of the Finnish paper industry. From theory building point of view, our empirical process data brings out, that the variation in the production lines were minimal, but there are big variations in paper deliveries, There are a lot to gain in the logistics processes. Larger volumes of the delivered tons also tend to increase profits. From the mill to the consignees, fluctuations in the process and paper sales grow substantially, which indicate longer storage times.
Research limitations/implications – The results of the case study are based on the data of one large integrated paper mill in Finland covering the years 2001-2007, so the results cannot be directly generalised to all Nordic paper mills. In May 2005, there was an industrial blackout, which affected considerably the production and deliveries from all the Finnish paper mills during that year.
Practical implications – The competitive advantages of the Finnish paper industry are weakened by the low paper prices and costly logistics. The mill managers should focus more on the overcapacity and cost issues and also deliver volumes, which all could contribute higher profits.
Originality/value – In this paper we study the Finnish paper industry together with time series, economic geography and statistical tools. This approach is a novel method and gives new insight for this research object. We study the mill’s economic variables as paper prices, profits and logistics and manufacturing costs and the characteristics of these issues in the spatial context. Purpose – The aim of this case study is to reveal the development of prices, costs and logistics in the case mill and how do these variables correlate with profits and finally to give suggestions for improvements.
Design/methodology/approach – We selected a typical Finnish paper mill as the basis for the case study. The mill data contains complete years from 2001 to 2007 on a monthly level. The data was obtained from the mill’s economic system and transferred to Excel. Statistica 4.1 was used to run the statistical correlation analyses. The results can be generalized with certain limitations to paper manufacturing located far from its customers.
Findings – This paper reveals an important insight on the economics of the Finnish paper industry. From theory building point of view, our empirical process data brings out, that the variation in the production lines were minimal, but there are big variations in paper deliveries, There are a lot to gain in the logistics processes. Larger volumes of the delivered tons also tend to increase profits. From the mill to the consignees, fluctuations in the process and paper sales grow substantially, which indicate longer storage times.
Research limitations/implications – The results of the case study are based on the data of one large integrated paper mill in Finland covering the years 2001-2007, so the results cannot be directly generalised to all Nordic paper mills. In May 2005, there was an industrial blackout, which affected considerably the production and deliveries from all the Finnish paper mills during that year.
Practical implications – The competitive advantages of the Finnish paper industry are weakened by the low paper prices and costly logistics. The mill managers should focus more on the overcapacity and cost issues and also deliver volumes, which all could contribute higher profits.
Originality/value – In this paper we study the Finnish paper industry together with time series, economic geography and statistical tools. This approach is a novel method and gives new insight for this research object. We study the mill’s economic variables as paper prices, profits and logistics and manufacturing costs and the characteristics of these issues in the spatial context.